Dermatophagoides pteronyssinus-induced pro-inflammatory responses mediated via STAT3 and NF-kappaB signaling pathways in human bronchial epithelial cells - Inhibitory effects of Lafoensia pacari and ellagic acid - Ana Letícia Júlio de Souza; Aline Beatriz Mahler Pereira; Jhony Robison de Oliveira; Luciana Santos Ramalho; Henrique Ismarsi de Souza; Altina Lacerda Nascimento; Mohib Uddin; Paulo Sérgio Pereira; David Nascimento Silva Teixeira; Paulo Roberto da Silva; Deijanira Alves de Albuquerque; Lucia Helena Faccioli; et al. (Elsevier, 2020)
The house dust mite allergen Dermatophagoides pteronyssinus (Der p) is a major driver of allergic asthma. Studies from our group demonstrated anti-eosinophilic effects of ethanolic extract of Lafoensia pacari stem bark (and ellagic acid, isolated from L. pacari extract), used as traditional medicine in Brazil to naturally treat inflammatory conditions. Here, we extended these results through performing phytochemical analysis of the constituents of L. pacari using liquid chromatography-mass spectrometry and evaluating the anti-inflammatory effects of both L. pacari and ellagic acid in the human BEAS-2B bronchial epithelial cell line stimulated with Der p. Ellagic acid (major constituent), gallic acid, ferulic acid, chlorogenic acid and rosmarinic acid, but not flavonoids (rutin, kaempferol, luteolin and quercetin), were found in the L. pacari. Pro-inflammatory mediators, IL-6, IL-8 and CCL-2 production were increased in BEAS-2B stimulated with Der p (10 μg/mL, 24 h) compared to control. L. pacari (250 μg/mL) and ellagic acid (100 μM) significantly reduced the concentration of these mediators. L. pacari increased the production of the anti-inflammatory cytokine, IL-10. These results were associated with the downregulation of NF-κB and STAT3 pathways. These findings indicate a novel anti-inflammatory action for L. pacari and ellagic acid in the airways allergic inflammatory response. Keywords: Allergic asthma, Human bronchial epithelial cells, Lafoensia pacari, Ellagic acid, Dermatophagoides pteronyssinus